The Effects of Varying Saffron Extract Concentration on the Physical Quality, Stability and Antioxidant Activity Tests of Gel Dosage Form - Pramasari, Nadia; Shoviantari, Fenita; Rumwarin, Yuliana; Yuliati, Ninis; Anjani, Ade Giriayu; Hesturini, Asih Imulda; Sugiyartono (Fakultas Farmasi, Universitas Surabaya, 2025)
Saffron (Crocus sativus L) is a plant that contains antioxidants, which is known as “red gold” and belongs to the iris family (Iridaceae). Saffron stigmas are reported to have antioxidant activity to prevent free radicals. This study aimed to determine the effects of varying saffron extract concentrations on the physical quality, stability, and antioxidant activity of the gel dosage form. There were 3 gel preparation formulations containing 1% (F1), 2% (F2), and 3% (F3) saffron extract. Physical quality tests for the saffron extract gel were included organoleptic test, homogeneity test, pH test, adhesion test, and spreadability test. A stability test was conducted at 25 ± 2°C for 1 month. Antioxidant activity test was performed using DPPH. The results of the physical quality tests, stability tests, and antioxidant tests were analyzed using SPSS. The results of the saffron extracts in gel F1, F2, and F3 met the requirements, and no differences in F1, F2, and F3. The stability test revealed differences in adhesiveness among F1, F2, and F3. The antioxidant activity test of the saffron extract gel dosage form was included in the moderate antioxidant category, with the IC50 values of formulation 1 (195.25 ppm), formulation 2 (178.31 ppm), and formulation 3 (159.26 ppm). The results of the antioxidant activity test on saffron extract also showed a moderate category. This study showed that all physical quality tests met the requirements, the preparation was unstable during storage, and the antioxidant activity was categorized as moderate.